Indonesian EFL Teachers' Identity Construction in a Global Englishes Era - M. Faruq Ubaidillah; Sonny Elfiyanto; Andri Jamaul Rifiyani; Huan Yik Lee (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2023)
Studies on English as a foreign language (EFL) teachers’ identity construction have been extensively investigated in recent years. However, the previous studies exclusively focused on teachers in higher education and neglected Global Englishes (GE) concept as a mediator in identity construction. Therefore, to fill this lacuna, the current narrative research study explored the identity construction of 10 Indonesian EFL secondary school teachers in the Global Englishes era. The data were gathered through in-depth interviews and observations and were analyzed using Braun and Clarke’s (2006) thematic analysis. Findings were elaborated into six emerging themes; they were 1) teachers’ perspectives of Global Englishes, 2) the goal of teaching English, 3) native speaker fallacy, 4) the use of mother tongue, 5) the use of Western cultures, and 6) the use of international English textbooks. Based on the investigation, the teachers echoed multiple identities as English teachers vis-à-vis the Global Englishes era. Although they are aware of such an issue, their tenets to adhere to the practice of native speaker fallacy are still strongly held. In other words, our study revealed a perceptual mismatch among the teachers with regard to their identities in a Global Englishes era.